Valoración de los alumnos del 5to. nivel sobre la formación profesional en negocios internacionales y turismo, FACEN - UNAP, 2021 - Cerron Diaz, Carla Patricia (2023)
The thesis developed is titled "Assessment of the students of the 5th. Level on professional training in international business and tourism, FACEN - UNAP, 2021", it has the objective of determining how much the competence indicators of the subjects received and valued from the cognitive, procedural and attitudinal aspect of the students who are studying the last academic year of the career of International Business and Tourism. Methodologically, it is a quantitative and applied study with a descriptive design. 45 surveys were applied to the regular students of the last cycle. The instrument was subjected to validation, obtaining a Cronbach's alpha = 0.8919 of excellent reliability, that is, the survey measures what is required to be measured. The statistical results show that the cognitive capacity is the most valued, it does not become significant, in the same way the procedural and attitudinal capacity do not have much difference in valuation. In the three capacities, the assessment "Quite" is the one that predominates. The hypothesis is rejected because the results of the assessments are statistically insignificant, so there is no further assessment of the academic training of the students of the 5th level of the professional school of International Business and Tourism.